2018
DOI: 10.1177/1557988317750943
|View full text |Cite
|
Sign up to set email alerts
|

Engaging the Underrepresented Sex: Male Participation in Chronic Disease Self-Management Education (CDSME) Programs

Abstract: Females are more likely than males to participate in evidence-based health promotion and disease prevention programs targeted for middle-aged and older adults. Despite the availability and benefits of Stanford’s Chronic Disease Self-Management Education (CDSME) programs, male participation remains low. This study identifies personal characteristics of males who attended CDSME program workshops and identifies factors associated with successful intervention completion. Data were analyzed from 45,375 male CDSME p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 24 publications
(32 reference statements)
1
22
0
Order By: Relevance
“…A study examining the predictors of participation in a chronic disease self-management (CDSM) programme indicated that physical ill health compromises participation [8]. Male gender is also associated with poorer participation in CDSM, although the results suggested that different venues and modes of delivery may improve participation [9]. Better knowledge of the factors that predict engagement with survivorship support programmes is important, given the potentially deleterious effects of non-engagement for patient wellbeing and survivorship.…”
Section: Introductionmentioning
confidence: 99%
“…A study examining the predictors of participation in a chronic disease self-management (CDSM) programme indicated that physical ill health compromises participation [8]. Male gender is also associated with poorer participation in CDSM, although the results suggested that different venues and modes of delivery may improve participation [9]. Better knowledge of the factors that predict engagement with survivorship support programmes is important, given the potentially deleterious effects of non-engagement for patient wellbeing and survivorship.…”
Section: Introductionmentioning
confidence: 99%
“…6). It has also been documented that screening is underutilized, as is timely follow-up on abnormal results in these populations (7)(8)(9)(10). Such disparities are likely attributable to sociocultural barriers including economic disadvantage, lack of insurance and provider continuity, and longer travel distances to care (3,(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…According to the SIGN checklist, 18 of the studies [ 7 , 20 , 28 , 30 , 31 , 33 , 35 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 49 , 55 ] were rated “high quality” and 17 studies were “acceptable quality” [ 5 , 6 , 15 , 19 , 29 , 34 , 36 , 46 , 47 , 48 , 50 , 51 , 52 , 53 , 54 , 56 ]. Although the studies were rated as being high and acceptable quality, for sample selection random assignment was used and no detailed description of the procedure was provided.…”
Section: Resultsmentioning
confidence: 99%